2013
DOI: 10.1111/ane.12157
|View full text |Cite
|
Sign up to set email alerts
|

Age at onset of amyotrophic lateral sclerosis in China

Abstract: This investigation confirmed the earlier age at onset of ALS in China as compared with other countries. Further population-based case-control investigations of genetic and environmental factors are needed to identify the potential risk factors for Chinese ALS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
36
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 30 publications
6
36
2
Order By: Relevance
“…Surely, on the basis of family and personal anxiety, younger patients would seek help more commonly than older patients, and older ones could have more difficulty visiting the clinic, which may create bias. However, a multicentre study in mainland China which recruited 455 patients from 10 centres showed that the mean age at onset for the entire cohort was 52.4±12.1 years, which was similar to that of our present study 20. The finding of this multicentre study made our result convincing and reliable.…”
Section: Discussionsupporting
confidence: 90%
“…Surely, on the basis of family and personal anxiety, younger patients would seek help more commonly than older patients, and older ones could have more difficulty visiting the clinic, which may create bias. However, a multicentre study in mainland China which recruited 455 patients from 10 centres showed that the mean age at onset for the entire cohort was 52.4±12.1 years, which was similar to that of our present study 20. The finding of this multicentre study made our result convincing and reliable.…”
Section: Discussionsupporting
confidence: 90%
“…It is argued that possible protective hormonal factors in women may be related to this observed rate [18]. In this study, there is no evidence of a significant decline in the male:female ratio among postmenopausal age groups.…”
Section: Discussioncontrasting
confidence: 49%
“…Reports from China have suggested that C9orf72 mutations are not a common cause of familial or sporadic ALS in Chinese mainland [17]. In addition, the life expectancy of the defined population may also affect the incidence of ALS; ­the average life expectancy in China is approximately 5 years shorter than that in developed countries [18]. Chinese population with fewer number of old people will partly lead to lower rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report [120] describing a Chinese ALS cohort suggested that epidemiological characteristics of Chinese MND patients were similar to those observed in international populations. However a separate investigation [111] confirmed the earlier age at onset of ALS in China as compared to Caucasian populations. In addition, the significantly low frequency of known ALS causing genes has been reported in Asian populations, including the rare mutations in C9orf72 and VCP.…”
Section: Discussionmentioning
confidence: 71%